Walk it off: predictive power of appendicular characters toward inference of higher‐level relationships in Laniatores (Arachnida: Opiliones). (23rd May 2013) - Gainett, Guilherme; Sharma, Prashant P.; Pinto‐da‐Rocha, Ricardo; Giribet, Gonzalo; Willemart, Rodrigo H.
Abstract Morphological characters are essential for establishing phylogenetic relationships, delimiting higher‐level taxa, and testing phylogenetic relationships inferred from molecular sequence data. In cases where relationships between large clades remain unresolved, it becomes imperative to establish which character systems are sound predictors of phylogenetic signal. In the case of Laniatores, the largest suborder of Opiliones, some superfamilial relationships remain unresolved or unsupported, and traditionally employed phenotypic characters are typically of utility only at the family level. Here we investigated a promising set of morphological characters that can be discretized and scored in all Opiliones: cuticular structures of the distal podomeres (metatarsi and tarsi). We intensively sampled members of all known families of Laniatores, and define here three new, discrete appendicular characters toward refinement of Laniatores superfamilial systematics: metatarsal paired slits (MPS; occurring in all Laniatores except Sandokanidae), proximal tarsomeric gland (PTG; in Icaleptidae, Fissiphalliidae, and Zalmoxidae), and tarsal aggregate pores (TAP; found in Gonyleptoidea, Epedanoidea, and Pyramidopidae). We conducted statistical tests on each character to characterize the strength of phylogenetic signal and assess character independence, based on alternative tree topologies of Laniatores. All three characters had high retention indices and bore significantly strong phylogenetic signal. Excepting one pairwise comparison, morphological characters did not evolve in a correlated manner, indicating that appendicular morphology does not constitute a single character system. Our results demonstrate the predictive power and utility of appendicular characters in Opiliones phylogeny, and proffer a promising source of diagnostic synapomorphies for delimiting superfamilies.